Entropy parameters for desiccant wheel design. (22nd January 2015) - Giannetti, Niccolò; Rocchetti, Andrea; Saito, Kiyoshi; Yamaguchi, Seiichi
Abstract: In this work a thermodynamic analysis of a desiccant wheel is proposed to investigate and identify the optimum size and operating regime of this device. A steady state entropy generation expression, based on effectiveness parameters suitable for desiccant wheels operability, is obtained applying a control volume approach and assuming perfect gas behaviour of the binary air–vapour mixture. A new entropy generation number N L is defined using a minimum indicative value of the entropy generation S L, min and investigated in order to obtain useful criteria for desiccant wheels optimization. The effectiveness-NTU design method is employed by combining solution of thermal exchange efficiency for rotary heat exchanger with the characteristic potential method, under the conditions of heat and mass transfer analogy. The analysis is applied to a specific desiccant wheel and N L variation with NTU is explored under various operative conditions and wheels characteristics in terms of dimensionless velocity and flow unbalance ratio. Highlights: Steady state entropy generation based on effectiveness parameters for heat and mass transfer. Definition of a new entropy generation number N L for desiccant wheel. Least irreversible features for a defined dehumidification rate of the desiccant wheel. N L can be used as an optimization parameter for desiccant wheels design and control.